Android Game-Based Learning Media Recognizes the Structure and Functions of Plant and Animal Parts for Elementary School - Endah Sudarmilah; Ikhwan Caesar Amri Pradana; Diah Priyawati (JUITA : Jurnal Informatika, 2022)
Teaching and learning activities in Indonesia still employ the lecture method which is considered traditional, therefore it is necessary to refresh it by utilizing learning media in teaching and learning activities. One of the methods applied is using learning media based on android game in which it puts forward user experience to its user. With this interesting educational game, children will not realize that what they are doing includes learning and children will feel happy and want to learn. This application is intended for the android smartphone platform. This development method uses Research and Development (R&D) with an Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The results of the black box test from the research are that this android game-based learning media can run well.